OPTIMASI PENINGKATAN KUALITAS TEPUNG LINDUR DENGAN PENAMBAHAN KONSENTRASI ASAM AMINO DAN ENZIM TRANSGLUTAMINASE - Muhammad Rahmad Ramadhan; Sapta Raharja; Sukardi Sukardi (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
In the wider application of lindur flour, it is necessary to improve the functional properties of flour. Cross-linking between amino acids and transglutaminase enzymes is an effort to improve functional properties to improve the quality of lindur flour. This study aims to optimize the process of modifying the cross-linking of two different factor variables, namely the concentration of amino acids (X1) and transglutaminase (X2) enzymes using response surface methodology analysis. The response variables were analyzed to obtain the optimum conditions, namely swelling power, solubility, protein content, and baking expansion. There are two tests in this study, namely initial characteristics testing including proximate analysis, starch content, amylose, amylopectin, swelling power and solubility, baking expansion, whiteness degree, and supporting tests including FTIR and SEM analysis. The optimum conditions obtained were amino acid concentrations of 12 % and the enzyme transglutaminase 8 U/g. The results of the optimum response variables were swelling power of 9.58 g/g, solubility of 23.15 %, protein content of 19.99 %, and baking expansion of 2.27 ml/g. SEM analysis of modified lindur flour showed that the morphological structure of the granules changed in size, shape and physical properties. FTIR analysis showed that there was a change in the O-H group to N-H and the strengthening of the C-N group which was thought to be due to cross-linking.